The representation of lexical units in the translation of french media texts into Uzbek - Karimova , Nilufar (The Lingua Spectrum, 2025)
This article analyzes the main challenges encountered in translating French media texts into Uzbek and examines how lexical units should be accurately conveyed. Media texts serve as a primary source of information disseminated to a broad audience through mass media, and their translation requires consideration not only of linguistic elements but also of the social and cultural contexts of the text. The article thoroughly explores the concept of interlingual equivalence and its significance in media text translation. Notably, Uzbek and French belong to different language families, and their lexical, grammatical, and syntactic differences pose additional difficulties for translators. The challenge is particularly evident in the translation of phraseological units, idioms, and culturally embedded words, where finding an appropriate equivalent is of crucial importance. Therefore, a translator must not only be a linguist but also act as a cultural mediator. Moreover, the article highlights the role of media text translation in the global communication and information exchange process. In the present era of information, the accuracy and clarity of translated texts directly impact the effectiveness of messages conveyed through mass media. From this perspective, translators should focus not only on finding precise equivalents but also on preserving the stylistic and functional aspects of the text. This article provides both theoretical and practical foundations for academic research and translation practice, offering valuable recommendations for translators. It emphasizes that overcoming challenges in media text translation and ensuring high-quality translation require a scientific approach, an understanding of cultural context, and linguistic expertise.